Video Profil Desa Sebagai Media Promosi Potensi Wisata Pedesaan - Saepudin, Encang; Sugito, Toto; Kokom Komariah (Journal Of Human And Education (JAHE), 2025)
Jemah Village offers various interesting tourist destinations, both in the form of natural beauty and man-made works. Therefore, Jemah Village has the potential to become a tourist village. To introduce the various potential tourist destinations, an interesting and effective promotional media is needed. Through the creation of an interesting and unique Village Profile Video, it is hoped that it can disseminate information about various potential tourist destinations in Jemah Village. The purpose of implementing community service is to provide knowledge and skills to Jemah Village officials in creating Village Profile Videos as a promotional media for rural tourism potential. The implementation method uses the Participatory Rural Appraisa approach, an approach that allows the community to jointly analyze the problems they face. The stages of implementing community service are the preparation, implementation and evaluation stages. The targets of implementing community service are village officials and members of the Jemah Village Karangtaruna. The results of implementing community service show that there is an increase in the knowledge and skills of the target community about making Village Profile Videos. This can be seen from the results of the video profile production work made by the training participants. From the results of the activities, it can be concluded that the implementation of community service that has been carried out can improve the knowledge and skills of participants in making Village Profile Videos